Midline Destructive Lesions of the Sinonasal Tract: Simplified Terminology Based onHistopathologic Criteria - Borges, Alexandra; Fink, James; Villablanca, Pablo; Eversole, Roy; Lufkin, Robert (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Destructive lesions of the sinonasal tract, lacking a discernible etiology and referred to as midline destructive disease, have been pathologically classified in accordance with a variety of confusing terms. Development of new pathologic concepts and immunohistochemical techniques has provided a fresh understanding of these lesions, and, as a result, they can be unified into two distinct pathologic groups: Wegener's granulomatosis and non-Hodgkin's T-cell lymphoma.METHODS: We retrospectively reviewed the imaging studies and pathologic specimens of seven patients with prior diagnoses included in the midline destructive disease group. The specimens were reviewed by an oral pathologist using currently accepted pathologic criteria and the newly available immunohistochemical markers CD20, CD45, and CD45RO. Lesions were classified as non-Hodgkin's T-cell lymphomas when positive for CD45 and CD45RO and negative for CD20, and as Wegener's granulomatosis in the presence of noncaseating multinucleated giant cell granulomas and necrotizing vasculitis.RESULTS: Three of the lesions were reclassified as Wegener's granulomatosis and four as T-cell lymphomas after applying these pathologic criteria. There were no distinguishing imaging findings between Wegener's granulomatosis and non-Hodgkin's T-cell lymphoma.CONCLUSION: The current pathologic classification for midline destructive disease should be incorporated into the radiologic lexicon and the use of terms from the old classification system, such as idiopathic midline granuloma and lethal midline granuloma, should be abandoned and no longer be used in radiologic reports.